2002
DOI: 10.1093/tropej/48.6.362
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Childhood Tuberculous Meningitis

Abstract: The risk factors affecting the outcome in 50 children with tuberculous meningitis were evaluated over a period of 20 months. Five children (10 per cent) had stage 1 disease, 29 (58 per cent) had stage II disease, and 16 (32 per cent) had stage III disease at admission. Seventeen cases (34 per cent) showed complete recovery, five (10 per cent) had mild, 14 (28 per cent) had moderate, and nine (18 per cent) had severe neurological sequelae. Five children (10 per cent) died. Younger age, tonic posturing, papilloe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
1
20
0
2
Order By: Relevance
“…9 Like in other studies, we found that TBM stage III was associated with increased mortality. 9,16,17 Our study was not powered to look for associations but those who had surgery, serial LPs, acetazolamine use and longer mean hospital stay had poor outcome of death and neurological sequelae. Similarly, longer hospital stay has been associated with poor outcome.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…9 Like in other studies, we found that TBM stage III was associated with increased mortality. 9,16,17 Our study was not powered to look for associations but those who had surgery, serial LPs, acetazolamine use and longer mean hospital stay had poor outcome of death and neurological sequelae. Similarly, longer hospital stay has been associated with poor outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Stage III is associated with worse outcome. 9,16,17 Availability of radiological tests like CT and MRI which were performed in 36/40 (90%) and were abnormal in 89% of cases further strengthened the diagnosis and then early treatment. Since TB prevalence is high in this region, TBM is always held in high suspicion and treatment was started early with good results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of them had attributed visual impairment with poor outcome [4,7]. Several authors reported that papilledema was associated with high mortality rate [22]. Amitava et al found complete ophthalmoplegia to be a strong predictor of mortality [4].…”
Section: Discussionmentioning
confidence: 99%
“…Overall mortality associated with TB meningitis is reportedly around 22 -39 %. 4,6 There have been few studies looking at the clinico-patho-radiological spectrum of TB meningitis in children from India. 7,8 In these backgrounds a study was conducted to look at the clinical outcome of children presented with TB Meningitis in a tertiary care centre in southern India by following them up and assess their present state in terms of neurological deficits, hearing and visual deficits, learning difficulties and day to day performances.…”
Section: Introductionmentioning
confidence: 99%